Latinoamerican Physics Education Network (LAPEN) and Modern Physics Teaching - Mora, César (Revista Cubana de Física; Vol 24 No 1 (2007): IV Ibero-American Workshop on Teaching of University Physics, 2007)
In this work we present the first activities of the Latin-American Physics Education Network (LAPEN) organized by representatives of Brazil, Cuba, Mexico, Argentina, Colombia, Uruguay, Peru and Spain. These activities include Seminars, Congress, Postgraduate Programs on Physics Education and several publications. The creation of LAPEN has been inspired and warranted by members of the International Commission of Physics Education (ICPE) of the International Union of Pure and Applied Physics. LAPEN was constituted in the International Meeting on Teaching Physics and Training Teachers (RIEFEP 2005) which was held in Matanzas, Cuba in November 2005. The creation of LAPEN was also warranted by the General Assembly of the IX Inter-American Conference on Physics Education held in San José, Costa Rica from 3 to 7 July 2006, and later by the ICPE-IUPAP in the International Conference on Physics Education 2006 in Tokyo, Japan. LAPEN is a network of academic networks in order to improve the physics education; finally we discuss the current overview of teaching physics in our region.